What is the best treatment for low HDL?. Issue 2 (February 2015) - Huber, Brian; Ludwig, Jennifer; Sheridan, Edward; Wyncott, David
Abstract : Evidence‐Based Answer : No high‐quality evidence is available regarding the impact of a low‐fat diet for patients with low high‐density lipoprotein (HDL). Moderate alcohol consumption may slightly increase HDL levels by less than 0.1 mmol/L. Medications including fibrates and HMG‐CoA reductase inhibitors increase HDL by 3% to 10% (SOR: C, disease‐oriented outcomes). In patients with both low HDL and low LDL with cardiovascular risk factors, pravastatin therapy reduces cardiovascular events by 4% over 6 years (SOR: B, RCT).